Challenges and lessons from COVID-19 - Om Saswat Sahoo; Dhar, Ruby; Arun Kumar; Subhradip Karmakar (Asian Journal of Medical Sciences, 2023)
In this review, we elaborate the post-COVID-19 challenges, and also, the lesson learned out of this crisis. With over 700 million people affected worldwide and nearly 6 million deaths, COVID-19 pandemic is of unprecedented nature ever witnessed by the human race. Besides health-care challenges, there were socioeconomic consequences that still have its footprints affecting life of the citizens. We summarized these challenges, addressing the lacunae in terms of enhancing our infrastructure, logistics, and knowledge, not only about this disease, but also to adequately prepare for future pandemic of this proportion.